2002
DOI: 10.1093/jnci/94.9.690
|View full text |Cite
|
Sign up to set email alerts
|

Host Circadian Clock as a Control Point in Tumor Progression

Abstract: Disruption of circadian rhythms in mice was associated with accelerated growth of malignant tumors of two types, suggesting that the host circadian clock may play an important role in endogenous control of tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
262
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(283 citation statements)
references
References 30 publications
14
262
0
7
Order By: Relevance
“…It is also associated with an increased incidence of several epithelial cancers (12-15). In mouse models, transplanted tumors grow twice as fast in scn-lesioned mice than in sham-lesioned animals (16). these studies have suggested a close connection between circadian organization and the development of various cancers.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is also associated with an increased incidence of several epithelial cancers (12-15). In mouse models, transplanted tumors grow twice as fast in scn-lesioned mice than in sham-lesioned animals (16). these studies have suggested a close connection between circadian organization and the development of various cancers.…”
Section: Introductionmentioning
confidence: 92%
“…relations between circadian genes and cancer have been demonstrated in recent years. the host circadian clock has been reported to play an important role in the endogenous control of tumor progression (16). As for circadian genes, Bmal1 was shown to be a positive regulator of tumor growth and metastasis in cancer (17).…”
Section: Introductionmentioning
confidence: 99%
“…[75][76][77][78][79]), and many of these signals are under circadian clock control [80,81]. An influence of systemic circadian signals is also indicated by experiments in which tumors were transplanted into animals with SCN ablations: the tumors grew faster in the SCN ablated animals than in normal controls [82]. These systemic signals might interact with peripheral clocks or function independently.…”
Section: Central Rhythms and Cell Proliferation: A Role For Hormones?mentioning
confidence: 99%
“…Ce syndrome est connu sous le nom de « non-24 hour sleep-wake cycle syndrome » [13]. Selon leur nature et leur degré, une perturbation ou un dysfonctionnement de l'horloge circadienne ont des implications physiologiques : effet de décalages horaires ou du travail posté, troubles de l'humeur, ou risques accrus de cancérogenèse [16,17]. L'effet des rythmes biologiques sur l'action des médicaments est l'objet des recherches en chronopharmacologie [18].…”
Section: Dysfonctionnements De L'horloge Circadienne Chez L'hommeunclassified